Pre-welding surface modification method suitable for aluminum oxide ceramic air reaction brazing

The surface of Al2O3 ceramics is modified through high-temperature hydrogen reduction technology, which solves the problems of poor wetting of ceramic surfaces and high residual stress of joints in air reaction brazing technology, achieves high strength and low residual stress of welds, and improves the overall performance of Al2O3 ceramic joints.

CN119591418AActive Publication Date: 2025-03-11SHENYANG LIMING AERO-ENGINE GROUP CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411589527.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-11
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The existing air reaction brazing technology has poor wetting properties on the surface of Al2O3 ceramics, which leads to the welds being prone to holes and other defects. The thermal expansion coefficients of the solder and ceramics are large, resulting in high residual stress and reduced strength of the joint.

Method used

The surface modification of Al2O3 ceramics is carried out by high-temperature hydrogen reduction technology to form dispersed ceramic particles, improve the surface roughness of the ceramic, promote the wetting of the solder, and form a composite phase zone of ceramic + solder during the brazing process to relieve residual stress and increase joint strength.

Benefits of technology

Modifying the surface of Al2O3 ceramics by high-temperature hydrogen reduction significantly improves the wetting properties of the solder and the strength of the welds, reduces the residual stress of the welding, and improves the overall performance of the Al2O3 ceramic joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591418A_ABST
    Figure CN119591418A_ABST
Patent Text Reader

Abstract

The invention discloses a pre-welding surface modification method suitable for aluminum oxide ceramic air reaction brazing, and belongs to the field of brazing, the pre-welding surface modification method comprises a high-temperature hydrogen reduction process and an air reaction brazing process, Al2O3 ceramic is subjected to a reduction reaction by means of the high reduction characteristic of H2 under the high-temperature condition, dispersed particles are formed on the surface of the ceramic, and the surface of the Al2O3 ceramic is subjected to surface modification. The surface roughness of the ceramic is improved, wetting of the oxide brazing filler metal is promoted, the brazing filler metal can permeate into the grain boundary of the surface of the ceramic, a brazing filler metal and ceramic composite phase region is formed on the interface, Al2O3 particles distributed in a dispersed mode are formed in a weld joint, and the strength of the joint is improved while the residual stress of the ceramic joint is relieved. In the brazing process, brazing filler metal permeates into the Al2O3 ceramic surface subjected to high-temperature hydrogen reduction, a ceramic and brazing filler metal composite phase region is formed, the welding residual stress caused by the difference of thermal expansion coefficients between a welding seam and ceramic is relieved, ceramic particles obtained through reduction are dispersed and distributed in the welding seam after welding, and the joint strength is improved in a dispersion strengthening mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of brazing, and in particular relates to a pre-welding surface modification method suitable for air reaction brazing of alumina ceramics. Background Art

[0002] High temperature resistant materials have always been the key materials restricting the manufacturing of hot end components of aerospace. Since World War II, high temperature resistant materials have developed from cast high temperature alloys, deformed high temperature alloys to cast single crystal materials. However, metal materials are limited by their melting points and their use temperature cannot reach the level of ceramic matrix composites. The ceramic matrix composites that are expected to be used in aircraft mainly include SiC-based ceramics and Al 2 O 3 Since SiC-based ceramics have poor oxidation resistance, which seriously affects their service life, they must be equipped with environmental barrier coatings when working in high-temperature gas environments for a long time, which is expensive. Therefore, people began to pay attention to Al-based ceramics with better oxidation resistance and lower cost. 2 O 3 Base ceramic. Al 2 O 3 Al-based ceramics have the characteristics of low density, high temperature resistance, and oxidation resistance. Compared with SiC-based ceramics, Al 2 O 3 The base ceramic has better environmental stability and can serve for a long time in a gas environment of 1000℃-1400℃.

[0003] Air reaction brazing is one of the common methods to solve the problem of oxide ceramic connection. This method uses the eutectic reaction between inert metal silver and certain oxides to configure oxide brazing materials with low melting points, such as Ag-CuO brazing materials. This brazing material can be widely used in Al 2 O 3 、ZrO 2 Air reaction brazing can be done in air environment, without vacuum or protective atmosphere, and has low requirements on equipment conditions. The welds formed have excellent oxidation resistance and corrosion resistance. It has been applied in the field of oxide fuel cells. However, air reaction brazing technology also has some problems. The first is that the oxide brazing material used in this technology is not suitable for Al 2 O 3 The wettability of ceramic surface is poor. Taking Ag-8CuO solder (CuO atomic fraction is 8%) as an example, its surface wettability is poor at 1000℃ Al 2 O 3 The stable wetting angle of the ceramic surface is 23°, and the wettability is poor, which leads to defects such as holes in the weld. Secondly, the thermal expansion coefficient of the brazing material and the ceramic is very different, and the brazing temperature is often ≥1000℃, which leads to Al 2 O 3The residual stress of ceramic joints is high and the strength is reduced. 2 O 3 The connection problem of ceramics is the future of Al 2 O 3 A key link in the base ceramic forming technology. Summary of the invention

[0004] The present invention utilizes H 2 It has strong reducing properties under high temperature conditions and is very effective for Al 2 O 3 The ceramic undergoes a reduction reaction, forming dispersed particles on the ceramic surface, improving the surface roughness of the ceramic, promoting the wetting of the oxide solder, and the solder can penetrate into the grain boundary of the ceramic surface, forming a solder + ceramic composite phase region at the interface, and forming dispersed Al in the weld. 2 O 3 Particles can relieve the residual stress of ceramic joints while improving the strength of the joints.

[0005] The present invention is suitable for Al 2 O 3 A method for pre-welding surface modification of ceramic air reaction brazing includes a high-temperature hydrogen reduction process and an air reaction brazing process, and the specific steps include:

[0006] (1) Al 2 O 3 The ceramics are placed in a porcelain boat, and the porcelain boat is placed in a quartz tube of a tubular electric furnace. The quartz tube is placed outside the tubular electric furnace, and H is introduced into the quartz tube. 2 After the air in the quartz tube is exhausted, heating begins. After the furnace temperature reaches the predetermined temperature, the quartz tube is pushed into the furnace. 2 O 3 The ceramics were subjected to high-temperature hydrogen reduction treatment. After the heat preservation was completed, the quartz tube was removed and the ceramic boat was placed in the cooling zone, and the H2 was stopped. 2 , use N instead 2 Exhaust residual H 2 .

[0007] (2) Using brazing filler metal to wet Al after high temperature hydrogen reduction treatment 2 O 3 Ceramic, wetting angle 15°.

[0008] (3) Use pine alcohol to prepare solder powder into solder paste and place it on Al 2 O 3 The ceramic and the inert ceramic surface to be welded are clamped and sent into the muffle furnace.

[0009] (4) First, heat to 400°C at a rate of 10°C / min and keep warm to facilitate the volatilization of pinene alcohol. Then continue to heat to a predetermined temperature at a rate of 10°C / min and keep warm. Then, reduce the temperature to 400°C at a rate of 10°C / min and turn off the heating. The furnace is cooled to room temperature.

[0010] Key points of the technical solution of the present invention:

[0011] High temperature hydrogen reduction process: Al 2 O 3 The high-temperature hydrogen reduction process of ceramics is carried out in a tubular electric furnace, where H 2 The flow rate range is 250ml / min-350ml / min, the reduction temperature range is 800℃-900℃, and the insulation time range is 1h-2h.

[0012] High temperature hydrogen reduction process formulation basis: According to experimental verification, H 2 Flow rate is lower than 250ml / min, or reduction temperature is lower than 800℃, Al 2 O 3 The reduction time required to form dense and dispersed ceramic particles on the ceramic surface will be greatly extended; 2 Flow rate is greater than 350ml / min, for Al 2 O 3 The ceramic reduction effect is not significantly improved, but it will waste H 2 ; Although the reduction temperature is greater than 900°C, the reduction time can be greatly shortened. However, once the reduction time exceeds the threshold of 1h, the ceramic particles are likely to fall off from the ceramic surface, making the high-temperature hydrogen reduction process window too narrow.

[0013] Air reaction brazing process: Air reaction brazing is carried out in a muffle furnace, wherein the brazing temperature ranges from 1010°C to 1060°C, and the brazing holding time is ≥ 20 minutes. The brazing material used in the present invention is Ag-8CuO.

[0014] The inert ceramic of the present invention comprises Al 2 O 3 Ceramic, Y 3 Fe 5 O 12 ceramics.

[0015] In the above step (3), Al 2 O 3 The ceramic and inert ceramic are clamped with a mold at a pressure of 2 kPa.

[0016] In the above step (4), the heating process is specifically as follows: firstly heat to 400°C at 10°C / min and keep warm for 10 minutes to facilitate the volatilization of pinene alcohol, then continue to heat to 1010°C-1060°C at 10°C / min and keep warm for 20 minutes, then reduce to 400°C at 10°C / min and turn off the heating, and cool the furnace to room temperature.

[0017] Air reaction brazing process formulation basis: According to experimental verification, the brazing temperature is less than 1010℃, and the brazing material has a strong affinity to Al 2 O 3 The penetration of ceramic surface is not obvious, the brazing temperature is greater than 1060℃, and the Al content in the weld is 2 O 3 The particles will agglomerate and lose the dispersion strengthening effect. The brazing holding time is less than 20 minutes. 2 O 3 Particles tend to aggregate on Al 2 O 3 Near the ceramic interface, the weld loses its dispersion strengthening effect.

[0018] In the present invention, Al reduced by high temperature hydrogen 2 O 3 Ceramics and Y 3 Fe 5 O 12 The average shear strength of the joints obtained by air reaction brazing of ceramics can reach 62MPa at room temperature.

[0019] Beneficial effects of the present invention:

[0020] 1. This scheme increases Al by high temperature hydrogen reduction 2 O 3 The roughness of the ceramic surface can promote the wetting of the solder on the ceramic surface.

[0021] 2. High temperature hydrogen reduction can reduce Al 2 O 3 The ceramic surface is dense, and during the brazing process, the brazing material can penetrate into the ceramic surface to form a mechanical bite, thereby strengthening the joint interface strength.

[0022] 3. During the brazing process, the brazing material can penetrate into the Al reduced by high temperature hydrogen. 2 O 3 On the ceramic surface, a composite phase region of ceramic + brazing filler metal is formed, which relieves the welding residual stress caused by the difference in thermal expansion coefficient between the weld and the ceramic. The reduced ceramic particles are dispersed in the weld after welding, which can improve the joint strength by dispersion strengthening. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) Al without high temperature hydrogen reduction 2 O 3Ceramic surface; (b) H 2 Al atmosphere at 800℃ for 1h 2 O 3 Ceramic surface; (c) H 2 Al atmosphere at 800℃ for 2h 2 O 3 Ceramic surface; (d) H 2 Al atmosphere at 900℃ for 1h 2 O 3 Ceramic surface;

[0024] Figure 2 Al without high temperature hydrogen reduction 2 O 3 Ceramics and Y 3 Fe 5 O 12 Microstructure of the joint obtained by ceramic air reaction brazing; (a) macrostructure of the joint; (b) Al 2 O 3 Ceramic interface organization;

[0025] Figure 3 Al reduced by high temperature hydrogen 2 O 3 Ceramics and Y 3 Fe 5 O 12 Microstructure of the joint obtained by ceramic air reaction brazing; (a) macrostructure of the joint; (b) Al 2 O 3 Ceramic interface structure. DETAILED DESCRIPTION

[0026] Embodiment: Using the technical solution of the present invention to connect inert ceramic Y with air reaction brazing 3 Fe 5 O 12 With high temperature hydrogen reduced Al 2 O 3 Ceramic as an example (connecting inert ceramic Y 3 Fe 5 O 12 The purpose is to exclude Al 2 O 3 Interference of ceramic base material on weld microstructure and joint mechanical properties).

[0027] Comparative Example 1: A method suitable for Al 2 O 3 The surface modification method before welding of ceramic air reaction brazing, the specific operation steps are:

[0028] (1) Ag-8CuO solder is used to wet Al at 1010℃ 2 O 3Ceramic, wetting angle 23°.

[0029] (2) Ag-8CuO solder powder was prepared into solder paste using pine alcohol and placed in Al 2 O 3 Ceramics and Y 3 Fe 5 O 12 The ceramic surfaces to be welded are clamped with a mold at a pressure of 2kPa and sent into a muffle furnace.

[0030] (3) The heating process is to heat to 400°C at 10°C / min and keep it for 10 minutes to facilitate the volatilization of pine alcohol, then continue to heat to 1010°C at 10°C / min and keep it for 20 minutes, then reduce the temperature to 400°C at 10°C / min and turn off the heating, and cool the furnace to room temperature.

[0031] (4) The structure of the welded joint is shown in the attached Figure 2 After shear test, the average shear strength of the welded joint at room temperature is 45MPa.

[0032] Example 1: A method suitable for Al 2 O 3 The surface modification method before welding of ceramic air reaction brazing, the specific operation steps are:

[0033] (1) Al 2 O 3 The ceramics were placed in a porcelain boat, and the porcelain boat was placed in a quartz tube of a tubular electric furnace. The furnace tube was pulled out so that the porcelain boat was located in the cooling zone outside the electric furnace. Then, H2 was introduced into the quartz tube at a flow rate of 250 ml / min. 2 After the air in the quartz tube is exhausted, start heating. When the furnace temperature reaches 800℃, push the quartz tube into the furnace. After 2h of heat preservation, push the quartz tube out and place the porcelain boat in the cooling zone, and stop introducing H. 2 , use N instead 2 Exhaust residual H 2 . Al reduced by high temperature hydrogen 2 O 3 Ceramic surface morphology see attached Figure 1 (c) Al without high temperature hydrogen reduction 2 O 3 Ceramic surface morphology Figure 1 (a), by H 2 Al atmosphere at 800℃ for 1h 2 O 3 Ceramic surface morphology Figure 1 (b).

[0034] (2) Ag-8CuO solder was used to wet Al2O3 at 1030℃ after high temperature hydrogen reduction. 2 O 3 Ceramic, wetting angle 15°.

[0035] (3) Ag-8CuO solder powder was prepared into solder paste using pine alcohol and placed in Al 2 O 3 Ceramics and Y 3 Fe 5 O 12 The ceramic surfaces to be welded are clamped with a mold at a pressure of 2kPa and sent into a muffle furnace.

[0036] (4) The heating process is to heat to 400°C at 10°C / min and keep it for 10 minutes to facilitate the volatilization of pinene alcohol, then continue to heat to 1030°C at 10°C / min and keep it for 20 minutes, then reduce the temperature to 400°C at 10°C / min and turn off the heating, and cool the furnace to room temperature.

[0037] (5) The structure of the welded joint is shown in the attached Figure 3 After shear test, the average shear strength of the welded joint at room temperature is 60MPa.

[0038] Example 2: A method suitable for Al 2 O 3 The surface modification method before welding of ceramic air reaction brazing, the specific operation steps are:

[0039] (1) Al 2 O 3 The ceramics were placed in a porcelain boat, which was then placed in a quartz tube of a tubular electric furnace. The furnace tube was pulled out so that the porcelain boat was located in the cooling zone outside the electric furnace. H2 was then introduced into the quartz tube at a flow rate of 350 ml / min. 2 After the air in the quartz tube is exhausted, start heating. When the furnace temperature reaches 900℃, push the quartz tube into the furnace. After 1h of heat preservation, push the quartz tube out and place the porcelain boat in the cooling zone, and stop introducing H. 2 , use N instead 2 Exhaust residual H 2 . Al reduced by high temperature hydrogen 2 O 3 Ceramic surface morphology see attached Figure 1 (d).

[0040] (2) Ag-8CuO solder was used to wet Al2O3 reduced by high temperature hydrogen at 1060℃. 2 O 3 Ceramic, wetting angle 15°.

[0041] (3) Ag-8CuO solder powder was prepared into solder paste using pine alcohol and placed in Al 2 O 3 Ceramics and Y 3 Fe 5 O 12 The ceramic surfaces to be welded are clamped with a mold at a pressure of 2kPa and sent into a muffle furnace.

[0042] (4) The heating process is to heat to 400°C at 10°C / min and keep it for 10 minutes to facilitate the volatilization of pinene alcohol, then continue to heat to 1060°C at 10°C / min and keep it for 20 minutes, then reduce the temperature to 400°C at 10°C / min and turn off the heating, and cool the furnace to room temperature.

[0043] (5) After shear testing, the average shear strength of the welded joint at room temperature is 62 MPa.

Claims

1. A pre-welding surface modification method suitable for air reaction brazing of alumina ceramics, characterized in that: Including high temperature hydrogen reduction process and air reaction brazing process.

2. A pre-welding surface modification method suitable for air reaction brazing of alumina ceramics according to claim 1, characterized in that: The following steps are involved: (1) Al2O3 ceramics are placed in a ceramic boat, and after the ceramic boat is placed in a quartz tube of a tubular electric furnace, the quartz tube is placed outside the tubular electric furnace, and then H2 is introduced into the quartz tube. After the air in the quartz tube is exhausted, heating is started. After the furnace temperature reaches a predetermined temperature, the quartz tube is pushed into the furnace to perform high-temperature hydrogen reduction treatment on the Al2O3 ceramics. After the insulation is completed, the quartz tube is taken out and the ceramic boat is placed in a cooling zone. The introduction of H2 is stopped, and N2 is used to exhaust the residual H2. (2) The brazing material is used to wet the Al2O3 ceramic treated by high temperature hydrogen reduction, and the wetting angle is 15°; (3) Using pine alcohol to prepare solder powder into solder paste, placing it between Al2O3 ceramic and the inert ceramic surface to be welded, clamping it, and sending it into a muffle furnace; (4) First heat to 400℃ and keep warm to facilitate the volatilization of pine oil, then continue to heat to the brazing temperature and keep warm, then reduce to 400℃ and turn off the heating, and cool the furnace to room temperature.

3. The method for pre-welding surface modification suitable for air reaction brazing of alumina ceramics according to claim 2, characterized in that: The high-temperature hydrogen reduction process of Al2O3 ceramics is carried out in a tubular electric furnace, where the H2 flow rate range is 250ml / min-350ml / min, the reduction temperature range is 800℃-900℃, and the insulation time range is 1h-2h.

4. The method for pre-welding surface modification suitable for air reaction brazing of alumina ceramics according to claim 2, characterized in that: Air reaction brazing is carried out in a muffle furnace, the brazing temperature range is 1010℃-1060℃, and the brazing holding time is ≥20min.

5. The method for pre-welding surface modification suitable for air reaction brazing of alumina ceramics according to claim 2, characterized in that: The solder used is Ag-8CuO.

6. The method for pre-welding surface modification suitable for air reaction brazing of alumina ceramics according to claim 2, characterized in that: Inert ceramics include Al2O3 ceramics, Y3Fe5O 12 ceramics.

7. The method for pre-welding surface modification suitable for air reaction brazing of alumina ceramics according to claim 2, characterized in that: The Al2O3 ceramic and the inert ceramic are clamped in a mold at a pressure of 2 kPa.

8. The method for pre-welding surface modification suitable for air reaction brazing of alumina ceramics according to claim 2, characterized in that: The specific heating process is as follows: first heat to 400°C at 10°C / min and keep warm for 10 minutes to facilitate the volatilization of pinene alcohol, then continue to heat to 1010°C-1060°C at 10°C / min and keep warm for 20 minutes, then reduce to 400°C at 10°C / min and turn off the heating, and cool the furnace to room temperature.

9. The method for pre-welding surface modification suitable for air reaction brazing of alumina ceramics according to claim 2, characterized in that: High temperature hydrogen reduced Al2O3 ceramics and Y3Fe5O 12 The average shear strength of the joints obtained by air reaction brazing of ceramics reaches 62MPa at room temperature.

Citation Information

Patent Citations

  • Method for increasing surface roughness of man-made diamond single crystal

    CN104529527A

  • Process for coating superabrasive particles with metal

    CN1439061A

  • Improvements in ceramic-to-metal seals

    GB540991A

  • Method for joining ceramic to metal

    JP1996245274A